Vplivni dejavniki poseka v zasebnih gozdovih Slovenije v obdobju 1995-2014 - Domen Češarek (Slovenian Forestry Institute, 2018)
We analyzed the characteristics of timber harvesting in private forests of Slovenia during the 1995-2014 period. The survey included forest sub-compartments that had been completely privately owned in the studied period (n = 16,234). With the multiple linear regression models we analyzed the influence of 9 natural, 4 forest-management and 3 socioeconomic variables on the amount of annual felling per hectare and the medium felled tree. We found that with the increase of the size of plots and forest property timber harvesting is increasing. Harvesting was positively influenced by the share of spruce in the growing stock, site productivity, distance to the forest edge, the openness and the share of beech in the growing stock. Harvesting was negatively influenced by inclination, distance to road and settlements, number of (co)owners, the share of spruce in the potential natural vegetation and the proportion of succession stages. The medium felled tree was positively influenced by site productivity, and most negatively by distance to the road.